Evaluating Charpy Impact Signals with Different Frequencies Using Power Spectrum Densities - Ali, Mohd Basri (Trans Tech Publications, 2011)
The dynamic responses of the standard charpy impact machine are experimentally studied using the relevant data acquisition system in order to obtain the impact response. The numerical analysis by means of the finite element method has been used to obtain the findings. The standard charpy modelling using the aluminium 6061 material and low carbon steel 1050 were used for extracting strain responses on the striker during the impact simulation. A power spectrum density (PSD) approach is then applied to convert a signal from the time domain to the frequency domain using the fast Fourier transform (FFT) method. Related parameters of different frequencies, different material, strain signals, power spectrum density (PSD) and the relationship between them were finally correlated and discussed. It was found that the modulus elasticity of materials and frequencies (sample rates) were proportional to the strain signals and PSD during impact simulation